Holocene relative sea level changes in the Västervik‐Gamlebyviken region on the southeast coast of Sweden, southern Baltic Sea. (5th October 2022) - Katrantsiotis, Christos; Dahl, Martin; Palm, Veronica; Rönnby, Johan; Andrén, Thomas; Andrén, Elinor
Abstract : We reconstruct the Holocene shore displacement of the Västervik‐Gamlebyviken area on the southeast coast of Sweden, characterised by a maritime cultural landscape and archaeological significance since the Mesolithic. Sediment cores were retrieved from four lake basins that have been raised above sea level due to the postglacial land uplift and eustatic sea level changes after the melting of the Fennoscandian Ice Sheet. The cores were radiocarbon dated and analysed for loss on ignition and diatoms. The isolation thresholds of the basins were determined using LiDAR data. The results provide evidence for the initiation of the first Littorina Sea transgression in this area at 8.5 thousand calibrated years before present (cal. ka BP). A relative sea level rise by ∼7 m a.s.l. is recorded between 8.0 and 7.5 cal. ka BP with a highstand at ∼22 m a.s.l. between 7.5 and 6.2 cal. ka BP. These phases coincide with the second and third Littorina Sea transgressions, respectively, in the Blekinge area, southern Sweden and are consistent with the final deglaciation of North America. After 6.2 cal. ka BP, the relative sea level dropped below 22 m a.s.l., and remained at ∼20 m a.s.l. until 4.6 cal. ka BP coinciding with the fourth Littorina Sea transgression in Blekinge. From 4.6 to 4.2 cal. ka BP, the shore displacement shows a regression rate of 10 mm a −1 followed by a slowdown with a mean value of 4.6 mm a −1 until 1.6 cal. ka BP, when the relative sea level dropped below 3.3 m a.s.l. The Middle to Late Holocene highstand and other periods of minor sea level transgressions and/or higher salinity between 6.2 and 1.7 cal. ka BP are attributed to a combination of warmer climate and higher inflow of saline waters in the southern Baltic Sea due to stronger westerlies, caused by variations in the North Atlantic atmospheric patterns.